Penile Microvascular Arterial Bypass Surgery: Indications, Outcomes, and Complications - Ricardo Munarriz (The Scientific World Journal)
Penile microarterial bypass surgery (MABS) may be the only treatment capable of restoring normal erectile function without the necessity for the chronic use of vasoactive medications or placement of a penile prosthesis. Lack of standardization in patient selection, hemodynamic evaluation, surgical technique, and limited long-term outcome data using validated instruments has resulted in this surgery being considered experimental. The members of the Erectile Dysfunction Guideline Update Panel reviewed the available MABS publications and only four of 31 manuscripts met the criteria for the Arterial Occlusive Disease Index patient. The total studied population of these four publications was 50, which was considered too small to determine if MABS is effective or not. Reported successful outcomes were 36-80 and 91% for inferior epigastric artery (IEA) to dorsal vein and IEA to dorsal artery MABS, respectively. We recently published the largest long-term outcome MABS study using validated questionnaires (71 men aged 30.5 ± 9.2 years; mean follow-up 34.5 ± 18 months). The mean pre- and postoperative total International Index of Erectile Function, erectile function domain, questions 3 and 4 scores were 35.5 ± 14.8, 13.7 ± 6.7, 2.2 ± 1.4, 2.1 ± 1.3, and 56.2 ± 16.6, 23.8 ± 6.6, 4.1 ± 1.4, and 3.9 ± 1.5, respectively. In addition, 55 and 73% of patients reported erectile function domain scores ≥26 and 21, respectively, and almost 90% of patients would recommend or undergo MABS again. In addition, changes in pre- and postoperative sexual distress scale scores and the Center for Epidemiologic Studies Depression Scale were statistically significant. More importantly, treatment satisfaction (EDITS) was very high, and 87% of patients would recommend the surgery to someone else and 88.7% reported a significant improvement in their erectile function. In patients with no vascular risk factors and pure cavernosal arterial insufficiency, MABS provides long-term improvements in erectile function, depression, and overall satisfaction.